Cracking the Code of Sciatica - A Review of the Sport Injury and Rehabilitation Literature - Szymczuk, Błażej; Iwan, Magdalena; Milczarek, Jakub; Trojanowski, Dominik; Adamiec, Ksawery; Kajzar, Magdalena; Rodak, Małgorzata; Nitka, Kamila; Piątkowska, Natalia; Smorońska-Rypel, Joanna (Quality in Sport, 2024)
Introduction: Chronic low back pain presents a significant challenge in healthcare, affecting numerous individuals globally. Despite the availability of various treatment options, optimal management remains elusive. This study aims to explore different treatment strategies for chronic low back pain, including exercise, pharmacological interventions, and emerging techniques in neural management. Aim of the Study: The aim of this study is to provide healthcare professionals with comprehensive insights into managing chronic low back pain. By examining the effectiveness and potential side effects of different treatment modalities, the study seeks to enhance clinicians’ understanding and decision-making in pain management. Brief Summary: Through a thorough review of literature and evidence-based analysis, this study discusses the role of exercise, medications, and neural management techniques in managing chronic low back pain. It evaluates the efficacy, safety, and potential benefits of each approach, offering valuable guidance for healthcare professionals in optimizing patient care. Conclusion: This study underscores the importance of adopting a multidisciplinary approach to managing chronic low back pain. By incorporating a range of treatment modalities, including exercise, pharmacological interventions, and emerging techniques, healthcare professionals can deliver personalized and effective care to patients. Enhanced knowledge and understanding of these strategies empower clinicians to address the complex challenges associated with chronic low back pain and improve patient outcomes.